PERGURUAN TINGGI AGAMA ISLAM TENTANG PERENCANAAN DAN PENGEMBANGAN LEMBAGA PENDIDIKAN TINGGI ISLAM: PERUBAHAN STAIN KE IAIN DAN PERUBAHAN IAIN KE UIN - Ery Nofrizal; Zainap Hartati; Asmawati (JIP: Jurnal Ilmu Pendidikan, 2026)
The institutional transformation of Islamic higher education in Indonesia constitutes a crucial aspect of educational planning and development within the national education system. The change from State Islamic Colleges (STAIN) to State Islamic Institutes (IAIN), and subsequently from IAIN to State Islamic Universities (UIN), represents not merely a change in nomenclature but a strategic expansion of academic mandates, institutional strengthening, and the integration of Islamic sciences with general sciences. This study aims to analyze the historical background of the STAIN–IAIN–UIN transformation, the urgency of planning and developing Islamic higher education institutions, and development strategies relevant to globalization and contemporary challenges. This research employs a qualitative descriptive approach through library research by examining academic literature, government regulations, and relevant policy documents. The findings indicate that institutional transformation is a strategic response to the advancement of science and technology, labor market demands, religious moderation, and the internationalization of higher education. Islamic higher education institutions are required to develop integrative curricula, enhance the quality of human resources, strengthen research and scientific publications, and implement professional and accountable governance. Through comprehensive planning and effective development strategies, Islamic higher education institutions are expected to serve as centers of academic excellence while preserving Islamic values in the global era